Evaluation of the Capability of Carbon Dioxide Greenhouse Gas Absorption Using Nano Bio-Activated Carbon of Crataegus Sanguinea Core - P Farhadi; H Ahmadpour kacho; HA Asgharnia; M Masomi (Majallah-i Dānishgāh-i ʻUlūm-i Pizishkī̄-i Bābul, 2019)
BACKGROUND AND OBJECTIVE: Considerable increase in carbon dioxide gas in the Earth's atmosphere has caused several problems such as increasing the temperature of the earth, droughts and sudden changes in the climate. The purpose of this study was to evaluate the capability of carbon dioxide as greenhouse gas absorption using activated nanobiocarbon from the Crataegus Sanguinea core. METHODS: In this experimental study, the carbon dioxide gas penetration time in three subgroups with pressure (5,10,15 bars), flow (5,10,15 ml/min) and temperatures (20,30,60 °C) at concentrations of 0 to 1 gr / ml through a carbon dioxide gas capsule in a fixed bed column filled with 2 g of adsorbent synthesized by a carbon dioxide gas sensor. The synthesized nano-biocarbon adsorbent from the Crataegus Sanguinea Core was pyrolysed at a temperature of 300 ° C and activated at 600 °C. The research data were examined with pseudo -first-order and pseudo-second-order models. FINDINGS: Significant increase in gas infiltration time was observed at 15 bars pressure (86.71±0.09 min, p<0.001), temperature of 20 ºC (67.68±0.13 min, p≤0.001) and flow of 5 ml/min (75.78±0.11 min, p≤0.001) was more than 5 bars (37.14±0.17 min) and 10 bars (60.33±0.27 min) and 30 °C (54.36±0.03 min) and 60 ºC (45.34±0.31 min) and 10 ml/min (53.8±0.13 min) and 15 ml/min (45.09±0.09 min) respectively. Both models fit well with a coefficient of R2>0.98 on empirical data from absorption. CONCLUSION: The results of the study showed that increasing pressure and decreasing temperature and flow increase the time of carbon dioxide penetration onto synthesized adsorbent.